2016
DOI: 10.1097/id.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Implant Marginal Bone Loss

Abstract: The marginal bone loss is affected by location of the implants (higher in the maxillary posterior region). In addition, excessive C/I and OT/I ratios increase marginal bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
1
21
4
1
Order By: Relevance
“…29 Six-year follow-up results of a clinical study 29 showed CBL to be significantly higher around implants placed in the posterior maxilla compared with the mandible. However, the current results showed no statistically significant difference in terms of clinical peri-implant parameters and CBL in the maxillae and mandibles in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…29 Six-year follow-up results of a clinical study 29 showed CBL to be significantly higher around implants placed in the posterior maxilla compared with the mandible. However, the current results showed no statistically significant difference in terms of clinical peri-implant parameters and CBL in the maxillae and mandibles in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate risk of bias (plausible bias that raises some doubt about the results) if one or more criteria were partly met or were assessed as unclear TA B L E 1 Excluded studies Cantilever data not retrievable Koller, Pereira-Cenci, and Boscato (2016); Ozgur, Kazancioglu, Demirtas, Deger, and Ak (2016); Mangano et al (2014); Ekfeldt, Zellmer, and Carlsson (2013); Degidi, Nardi, and Piattelli (2013); Wittneben et al (2014); Heschl et al (2012); Ortorp and Jemt (2012); Malo, de Araújo Nobre, Lopes, Moss, and Molina (2011);Krennmair, Seemann, Schmidinger, Ewers, and Piehslinger (2010); Eliasson et al (2010); Davó (2009);Isaksson, Becktor, Brown, Laurizohn, and Isaksson (2009);Degidi, Iezzi, Perrotti, and Piattelli (2009); Ortorp and Jemt (2009);Gualini, Gualini, Cominelli, and Lekholm (2009);Blanes, Bernard, Blanes, and Belser (2007); Rasmusson, Roos, and Bystedt (2005); Hartman and Cochran (2004); Åstrand et al (2004); Attard and Zarb (2004); Ekelund, Lindquist, Carlsson, and Jemt (2003); Murphy, Absi, Gregory, and Williams (2002); Raghoebar, Timmenga, Reintsema, Stegenga, and Vissink (2001); Tinsley, Watson, and Russell (2001);Brägger, Aeschlimann, Bürgin, Hämmerle, and Lang (2001);Friberg, Gröndahl, Lekholm, and Brånemark (2000); Becker and Kaiser (2000); Schwartz-Arad, Gulayev, and Chaushu (2000); Arvidson, Bystedt, Frykholm, von Konow, and Lothigius (1998); Schwartz-Arad and Chaushu (1998); Keller, Tolman and Eckert (1998);Parein, Eckert, Wollan, and Keller (1997); …”
Section: Riskofbiasassessmentmentioning
confidence: 99%
“…the risk of screw and/or screwdriver aspiration during the placement of screw-retained implant restorations particularly in the posterior jaw cannot be overlooked. Six-year follow-up clinical results by Ozgur et al,31 showed significantly higher CBL around implants positioned in posterior maxilla compared with mandible. Six-year follow-up clinical results by Ozgur et al,31 showed significantly higher CBL around implants positioned in posterior maxilla compared with mandible.…”
mentioning
confidence: 94%
“…Although screw-and cement-retained restorations offer advantages as well as risks, the final choice of type of implant restoration protocol is dependent on the clinician's choice.It has been reported that the quality and density of bone varies between the maxilla and mandible, primarily due to the presence of sinuses in the former bone type 31. Although screw-and cement-retained restorations offer advantages as well as risks, the final choice of type of implant restoration protocol is dependent on the clinician's choice.It has been reported that the quality and density of bone varies between the maxilla and mandible, primarily due to the presence of sinuses in the former bone type 31.…”
mentioning
confidence: 99%